Kreativitas Guru Fikih dalam Menggunakan Media Pembelajaran Digital di Madrasah Aliyah Negeri Pematang Siantar-Sumatera Utara - Nurul Huda; Nasrun Salim Siregar (Jurnal Eduslamic, 2026)
This study aims to describe teachers’ creativity in utilizing instructional video media in teaching Fiqh at MAN Pematang Siantar. The study employed a qualitative approach with a case study design. The research subjects consisted of one Fiqh teacher as the main informant and two students as supporting informants. Data were collected through interviews, observations, and documentation, while data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. This study is grounded in the Technological Pedagogical Content Knowledge (TPACK) framework, supported by the SAMR model, as well as Multimedia Learning theory, which explains the use of technology and visual media in enhancing students’ understanding. The findings reveal that teachers’ creativity is reflected in their ability to design and utilize instructional videos in alignment with learning objectives. The videos are used to visualize the procedures of funeral prayer (shalat jenazah), enabling students to better understand the sequence of movements and recitations. Furthermore, the use of video media increases students’ engagement and comprehension during the learning process. Therefore, teacher creativity is not merely about the use of technology, but also about the ability to design contextual and meaningful learning experiences